Optimization of the Coupling Coefficient of the Inductive Link for Wireless Power Transfer to Biomedical Implants - Jiarui Bao; Shuyan Hu; Zibin Xie; Guangxi Hu; Ye Lu; Lirong Zheng (International Journal of Antennas and Propagation)
This work focuses on the optimization of coupling coefficient (k) of the inductive link for the wireless power transfer (WPT) system to be used in implantable medical devices (IMDs) of centimeter size. The analytic expression of k is presented. Simulations are conducted by using the high-frequency structure simulator (HFSS). Analytic results are verified with simulations. The receiving (Rx) coil is implanted in the body and set as a circular coil with a radius of 5 millimeters for reducing the risk of tissue inflammation. The inductive link under misalignment scenarios is optimized to improve k. When the distance between the transmitting (Tx) and Rx coils is fixed at 20 mm, it is found that, to maximize k, the Tx coil in a planar spiral configuration with an average radius of 20 mm is preferred, and the Rx coil in a solenoid configuration with a wire pitch of 0.7 mm is recommended. Based on these optimization results, an inductive link WPT system is proposed; the coupling coefficient k, the power transfer efficiency (PTE), and the maximum power delivered to the load (MPDL) of the system are obtained with both simulation and experiment. Different media of air, muscle, and bone separating the Tx and Rx coils are tested. For the muscle (bone) medium, PTE is 44.14% (43.07%) and MPDL is 145.38 mW (128.13 mW), respectively.